Technoestress and the lack of support from organizations for the adaptation of professionals to home working and its effects - Justino Ribeiro Mello, Andréa (2024)
Introduction: The pandemic has increased the psychological risks associated with home working, due to the significant intensification of its use. Therefore, we sought to verify the significance of pandemic variables – proposed from the literature review – in analysis models related to technostress and home working, taking into account its effects on satisfaction and happiness with work, on the desire to stay at work and on career stress. Methods: Based on Ragu-Natha et al. (2008) model, the questionnaire used to collect data addressed three technostressors: technoinvasion, technooverload and technouncertainty. In addition to these, pandemic variables were included in the analysis models developed and the relationship between these and technostressors with job satisfaction, happiness with work, the desire to stay in the job and career stress was verified. The questionnaire followed the Likert scale standard, and was sent to respondents by email and WhatsApp, resulting in 188 valid responses from Brazilian professionals who had adopted remote work due to the Covid-19 pandemic. The data obtained were analyzed using the R software and using the Ordinal Logistic Regression technique. Results: Factors related to technooverload and technoinvasion were confirmed as stressors and pandemic factors were significant for the analysis of technostress. Conclusion: Job satisfaction, happiness with work, the desire to stay in the job and career stress were influenced by the variables that compose technostress and also by the variables related to the context of the pandemic, especially the lack of support from organizations for the adaptation to home working.